Short- and mid-term effects of empagliflozin on sodium balance and fluid regulation in chronic heart failure - Bytyqi, Venera; Kannenkeril, Dennis; Kolwelter, Julie; Linz, Peter; Bosch, Agnes; Striepe, Kristina; Karg, Marina V.; Nagel, Armin Michael; Uder, Michael; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (European Journal of Heart Failure, 2025)
Aims: Sodium–glucose co-transporter 2 inhibitors have become a cornerstone in managing chronic heart failure (CHF). While their acute impact on urinary glucose and sodium excretion is well-established, their mid- and long-term persistence of these effects remains uncertain. This study investigated fluid and sodium balance over 3 months in a randomized, placebo-controlled trial (NCT03128528). Methods and results: Overall, 74 patients with New York Heart Association class II–III CHF and an ejection fraction (EF) ≤49% were randomized (2:1) to empagliflozin 10 mg (n = 48) or placebo (n = 26). Sodium, potassium, glucose, urea, and urine were determined from standardized 24-h urine collections. Free water clearance (FWC) and plasma/urine osmolality were calculated. Body weight was measured, and dedicated sodium magnetic resonance imaging (23Na-magnetic resonance imaging) was performed to quantify skin and muscle sodium levels at baseline, at 1 month, and at 3 months. Patients (mean age 66.4 years; 84% male; EF 40%; baseline N-terminal pro-B-type natriuretic peptide 707.9 pg/ml) were followed up at 1 and 3 months. Empagliflozin significantly increased natriuresis at 1 month (p = 0.040), while natriuresis returned to baseline by 3 months. Skin sodium content decreased at 1 month (p = 0.039) and remained reduced at 3 months (p = 0.013), while muscle sodium was unchanged. Persistent glucosuria (p < 0.001) increased urine osmolality at 3 months (p = 0.003). Urine volume increased transiently at 1 month (p = 0.046) but normalized by 3 months. Empagliflozin-treated patients showed a reduction in FWC at 1 and 3 months (p < 0.001), with a compensatory rise in copeptin levels, indicating increased vasopressin activity (1 month: p = 0.020; 3 months: p = 0.001). Conclusions: Mid-range effects of empagliflozin in heart failure with reduced EF include transient natriuresis and sustained glucosuria, with compensatory reductions in FWC. Reductions in skin sodium content were maintained, and volume homeostasis in CHF patients stabilized after 3 months.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Chronic heart failure; Empagliflozin; Fluid regulation; Renal adaptation; Sodium balance